Recent Advances in 3D Printing of Polyhydroxyalkanoates: A Review - Kovalcik Adriana (The EuroBiotech Journal, 2021)
In the 21st century, additive manufacturing technologies have gained in popularity mainly due to benefits such as rapid prototyping, faster small production runs, flexibility and space for innovations, non-complexity of the process and broad affordability. In order to meet diverse requirements that 3D models have to meet, it is necessary to develop new 3D printing technologies as well as processed materials. This review is focused on 3D printing technologies applicable for polyhydroxyalkanoates (PHAs). PHAs are thermoplastics regarded as a green alternative to petrochemical polymers. The 3D printing technologies presented as available for PHAs are selective laser sintering and fused deposition modeling. Stereolithography can also be applied provided that the molecular weight and functional end groups of the PHA are adjusted for photopolymerization. The chemical and physical properties primarily influence the processing of PHAs by 3D printing technologies. The intensive research for the fabrication of 3D objects based on PHA has been applied to fulfil criteria of rapid and customized prototyping mainly in the medical area.